Eponímia e tradução no campo biomédico: estudo num corpus de textos paralelos sobre medicamentos órfãos (en, fr e es) - Varela Vila, Tamara (2023)
This paper focuses on the study of eponyms in biomedical texts with a double objective: to obtain data on their presence in current texts and on the strategies used for their translation. For this purpose, a parallel corpus integrating three languages (English, Spanish, French) has been compiled and analyzed. The multigeneric nature of the textual samples that compose it (summary of product characteristics and package leaflets), its recent publication date (6 years ago) and the current socio-health issues that characterize the subdomain on which it is focused (orphan drugs) due to its link with rare diseases, make the corpus interesting and give it characteristics that are in line with the proposed objectives. After reviewing the most outstanding studies on the concept of eponymy, the corpus and the methodology used for its exploitation are presented. The results confirm that eponymy, despite the controversial nature of its use, is very frequent in the texts studied. Likewise, they indicate that the eponyms used are similar in the three languages analyzed, although there are slight divergences that should be analyzed in detail.